2003
DOI: 10.2307/4003895
|View full text |Cite
|
Sign up to set email alerts
|

Hay-Meadows Production and Weed Dynamics as Influenced by Management

Abstract: Managers of extensive livestock systems generally have 2 goals for permanent grassland management: to obtain sufficient dry matter to feed animals and to avoid the establishment and dominance of unpalatable species. Hay production in French Pyrenean meadows is dependant on the need to balance grazing and cutting dates to produce maximum biomass for hay stock and to prevent seed recruitment of Chaerophyllum aureum L., one of the major invasive unpalatable species. Experiments and observations on a set of meadow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…The fodder quality values of Taraxacum officinale have already been pointed out in previous works [5,7,66]. Regarding Chaerophyllum aureum, Magda et al [50] reported that it is palatable only at a very early stage, due to the concentration of lignified tissues in its shoots. Its ADL values in this work were not a limiting factor for its quality, as it had the third highest DDM value.…”
Section: Feeding Evaluationmentioning
confidence: 76%
See 2 more Smart Citations
“…The fodder quality values of Taraxacum officinale have already been pointed out in previous works [5,7,66]. Regarding Chaerophyllum aureum, Magda et al [50] reported that it is palatable only at a very early stage, due to the concentration of lignified tissues in its shoots. Its ADL values in this work were not a limiting factor for its quality, as it had the third highest DDM value.…”
Section: Feeding Evaluationmentioning
confidence: 76%
“…It was observed that some forage plants which have traditionally been assigned a value of zero quality were voluntarily selected for consumption by the animals, such that their palatability may be underestimated in the pastoral value method [40]. Of the nine species that did not appear in the list of Farruggia et al [41], we also found evidence of grazing consumption for Cerastium fontanum [48], Anthyllis vulneraria [49], Chaerophyllum aureum [50], and Heracleum sphondylium [21].…”
Section: Species Diversity and Qualitymentioning
confidence: 77%
See 1 more Smart Citation
“…The start of stem elongation, which is probably related to photoperiod, is a key variable, because defoliation after this stage leads to a leafy regrowth with a slower herbage growth rate than for reproductive growth (Duru et al. , 2002; Magda et al. , 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of non‐removal of the apex in spring, late defoliation allows sexual reproduction of grassland species. Populations of desirable and undesirable species, which depend exclusively on sexual reproduction to maintain their populations, can be limited according to whether hay‐making occurs before or after seed dispersal (Magda et al. , 2003).…”
Section: Introductionmentioning
confidence: 99%